Germany : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that Germany's economy is poised for a fragile recovery, after having barely grown since mid-2000. The earlier price shocks and interest rate hikes that contributed to the current slowdown have now unwound. However, sluggish global growth, stock market declines, weak credit growth, and the withdrawal implied by planned fiscal consolidation may stand in the way of a strong recovery. Real GDP growth in 2002 is estimated at about 0.5 percent, with the general government deficit set to exceed 3 percent of GDP.